PENGARUH TTS DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA DI KELAS IV SDN 2 TILANGO - Nyoman Ariani; Gamar Abdullah; Rustam I Husain (JAMBURA Elementary Education Journal, 2022)
Ariani, Nyoman. 2020. The Effect of Crossword Puzzle Media and Learning Motivation towards Student’s Learning Outcome on Life Cycle and Its Preservation Materials at IV Class of SDN 2 Tilango, Gorontalo District. Skripsi. Study program of Elementary Teacher Education, Faculty of Education, State University of Gorontalo. The principal supervisor is Gamar Abdullah, S.Si., M.Pd, and co supervisor is Dr. Rustam I. Husain, S.Ag., M.Pd. The research problems include 1) is there any difference in learning outcomes between student of IV class who are applied crossword puzzle media and students who are not at SDN 2 Tilango?; 2) for high learning motivation, is there any difference in learning outcomes between students of IV class who are applied crossword puzzle media and students who are not at SDN 2 Tilango?; 3) for low learning motivation is there any difference in learning outcomes between students of IV class who are applied crossword puzzle media and students who are not at SDN 2 Tilango?; 4) is there any effect of interaction of crossword puzzle media in classroom activites and learning motivation towards students’ learning outcomes at IV class of SDN 2 Tilango?. The research applies treatment by level 2x2 design while the research subject is students at IV class of SDN 2 Tilango. The research findings revealed that the application of crossword puzzle media had increased students’s learning outcome compared to those who did not use crossword puzzle. High learning motivation: students who applied crossword puzzle media had higher learning outcome than students who where not. Low learning motivation: students who were applied crossword puzzle media had higher learning outcome than students who were not. Crossword puzzle media had significant influence on students’ learning outcome and level of motivation. It can be proved by higher students’ average scores at IV class compared to another class. Therefore, the application of crossword puzzle media can be used in science learning process particularly on life cycle and its preservation materials.